Reliability Measurement of Control and Instrumentation Systems of Nuclear Power Plants - Singh P.; Singh L.K. (My University, 2025)
Control and instrumentation (C&I) systems are used to measure the critical parameters to take decisions and, hence, such systems do have high reliability target. Therefore, it is essential to measure the reliability of such systems with high accuracy. Petri net (PN) is a mathematical tool that can model the stochastic behavior of the systems. The research work is devoted to propose a framework to measure the reliability of these systems using PN. The proposed framework contains three phases: 1) state-space identification, 2) probability of a system being in each state, and 3) reliability measurement. The proposed approach has been applied to 21 C&I systems of nuclear power plant (NPP) and is demonstrated on a case study of NPP to prove its effectiveness. © 1963-2012 IEEE.